Implementasi Pinjam-Meminjam Dengan Jaminan Fidusia di Koperasi Simpan Pinjam Sahabat Mitra Sejati di Kota Jayapura - Baransano, Karel V. H. (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to determine the procedures for implementing lending and borrowing with fiduciary guarantees at the Sahabat Mitra Sejati Savings and Loan Cooperative (KSP) in Jayapura City and to determine the problems that arise in the implementation of lending and borrowing agreements with fiduciary guarantees at the Sahabat Mitra Sejati Savings and Loan Cooperative (KSP) in Jayapura City. The method used in this study is normative and empirical juridical, namely reviewing the laws and regulations including the 1945 Constitution of the Republic of Indonesia, the Civil Code, Law Number 25 of 1992 concerning Cooperatives, Government Regulation Number 9 of 1995 concerning the Implementation of Savings and Loan Business Activities by Cooperatives, and Law Number 42 of 1999 concerning Fiduciary Guarantees as well as observing the reality that occurs in the field. The results of this study reveal that the implementation of lending and borrowing with fiduciary guarantees at the Sahabat Mitra Sejati Savings and Loans Cooperative (KSP) is through the formation of a lending and borrowing agreement and a fiduciary burden agreement and the problems that arise in the implementation of the lending and borrowing agreement with fiduciary guarantees at the Sahabat Mitra Sejati Savings and Loans Cooperative (KSP) are the existence of default (defective performance), where the Debtor does not keep his promise to the Creditor as agreed by both parties in the credit agreement.